LOCAL FOOD PROCUREMENT TENDENCIES IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The OECD has emphasized that regions need to boost their growth by placing local resources and means in circulation in order to benefit from their competitive advantages. It encourages the search and analysis of those regional key factors that are driving development in the regions. Local authorities can boost their region with the use of territorial capital and the promotion of entrepreneurship. One of the ways how to do this is to buy food from local producers. Giving preference to local suppliers, even if it means spending a little more, can actually benefit a region’s finances. When local governments spend their money on locally owned firms, those firms in turn rely on and generate local supply chains, creating an “economic multiplier” effect. Each additional dollar that circulates locally boosts local economic activity, employment and, ultimately, tax revenue. In Latvia, since 2014, attention has been focused on increasing the consumption of local food. Improvements in regulatory enactments have been made, which stipulate that green public procurement criteria should be used in food procurement, where one of the criteria, the supply distance, directly contributes to this aim by giving preference to the local producers. The research aim is to analyze the data of local government food procurements carried out in Latvia from 2010 to 2018 and to evaluate the share of local suppliers in these procurements. The food procurement winners were divided into four groups: agricultural producers, food processing companies, wholesale companies and retail companies. The study evaluates how each group's share in total food purchases varies over the years, and how procurement volumes vary depending on the winner's belonging to the one of the groups previously defined. Such an analysis shows the proportion of local producers in procurement, but does not fully reflect on the volume of local production, as it is not possible to obtain data on the share of production which producer purchased from others to provide the necessary volumes of food, and there is no data on the origin of products supplied by wholesalers. The following research methods were employed to carry out the present research: analysis and synthesis, induction and deduction, the monographic method, statistical analysis and the graphic method.